Pengaruh Model Pembelajaran Mastery Learning terhadap Hasil Belajar Siswa Pendidikan Agama Kristen dan Budi Pekerti Kelas VIII SMP N 1 Sipahutar Tahun Pembelajaran 2024/2025 - Afni Sridevi Pardede; Rusmauli Simbolon; Julita Herawati; Limmarten Simatupang; Robert Simangunsong (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
The purpose of this study was to determine the effect of Mastery Learning Model on learning outcomes of Christian Religious Education and Budi Pekerti Learning Year 2024/2025. The research hypothesis is: "There is an Effect of Mastery Learning Model on Student Learning Outcomes of Christian Religious Education and Budi Pekerti class VIII SMP Negeri 1 Sipahutar Learning Year 2023/2024." The population is all VIII grade students of SMP Negeri 1 Sipahutar for the 2024/2025 Learning Year, totaling 252 people. The research sample was determined with a purposive sampling system, namely VIII-2 class students totaling 31 people as an experimental class using the Mastery Learning Model and VIII-1 class totaling 31 people as a control class that did not use the Mastery Learning Model. This research method is a quantitative approach with a true experimental design method and with a posttest only control group design. The instrument used in this research is a test question as many as 30 questions. Research data for questionnaires were analyzed using the Pooled Variance t test formula. From the calculation results obtained t count value = 13.727 > t table(α = 5%) = 2.000. The tcount value is in the H0 rejection and Ha acceptance curve area. Thus it can be concluded that the research hypothesis is accepted, namely that there is an effect of the Mastery Learning Model on the Learning Outcomes of Christian Religious Education Students and Budi Pekerti class VIII SMP Negeri 1 Sipahutar Learning Year 2024/2025. The difference in learning outcomes of Christian Religious Education and Ethics students in class VIII SMP Negeri 1 Sipahutar in the 2024/2025 Learning Year is known from the average learning outcomes of Christian Religious Education and ethics students by using the Mastery Learning Model is 28.06 higher than the average learning outcomes of Christian Religious Education and ethics students by not using the Mastery Learning Model which is 21.77.